Double spatial correlations, a new experimental insight into wall turbulence - Stanislas, Michel; Carlier, Johan; Foucaut, Jean-Marc; Dupont, Patrick (Comptes rendus de l'Académie des sciences. Série IIb, Mécanique, physique, astronomie, 1999)
The development of modern measurement techniques based on lasers and computers allows researchers today to access mathematical tools which were the subject of theoretical developments in the early stage of research on turbulence. The interest of double spatial correlations obtained from experiments is illustrated in the case of turbulent boundary layers. Le développement de techniques de mesures modernes fondées sur l'utilisation des lasers et de l'ordinateur permet aujourd'hui d'accéder à des outils mathématiques qui ont fait l'objet de développements théoriques au début des recherches sur la turbulence. L'intérêt des corrélations spatiales doubles tirées de l'expérience est illustré dans le cas de la couche limite turbulente.